Alam Bina Newsletter: vol. 9 2023 / College of Built Environment, Universiti Teknologi MARA - Universiti Teknologi MARA, College of Built Environment (College of Built Environment, 2023)
The articles within these pages encapsulate the spirit of adaptability that has become synonymous with CBE. From innovative approaches in education to the remarkable achievements of their students and faculty members, each story reflects their unwavering dedication to shaping futures and unleashing potential.